The Implementation of Cybernetic Learning to Improve Elementary School Students’ Learning Outcomes in SKI Subjects - Diana, Ega; Ananda, Rusydi; Sintiya, Sindy; Harahap, Khairunnisa; Dani, Sulis Mawar; Azhar, Muhammad (Jurnal Basicedu, 2023)
This study aims to describe the implementation of cybernetic theory learning in improving student learning outcomes in the SKI subject at MIN 3 Langkat. This type of research is qualitative with a descriptive study method, meaning that the researcher seeks to describe the actual phenomenon through a description of the sentence about the topic of study. Collecting data using the method of observation, interviews, and documentation studies. Data analysis using data reduction techniques, data presentation, and drawing conclusions. Furthermore, this research data is declared valid if it meets the criteria of credibility, dependability, and confirmability. The results of this study concluded that learning based on cybernetic theory makes it easier for students to manage information or learning messages, so that students focus on optimizing the learning process. Through an information system and prioritization of the learning process, student learning outcomes in SKI subjects at MIN 3 Langkat have increased. This can be seen from the value of the report card and the quality of student behavior with character.